Chile. - Vicuña, Magdalena; Orellana, Arturo (Routledge, 2018)
Objective is to target the "state of the art" of planning interventions as well as contemporary forms of planning knowledge and academic scholarship across the region. In doing so, a number of key themes are identified through rationales ranging from the emergence of planning policies, practices and discourses to gaps between theory and practice, and then moving on to the state of planning education and the exchange of planning knowledge across different countries within the region.
Keywords: Stadtentwicklungsplanung; Stadtplanung; Raumplanung; Planungssystem; Planungspraxis; Planungstheorie; Planerausbildung; Internationaler Vergleich; Länderbericht; Überblick